Pacific food systems The role of fish and other aquatic foods for nutrition and health - O'Meara, Lydia; Cohen, Philippa; Kafa, Rosemary I’ilu; Wate, Jillian Tutuo; Albert, Joelle; Bogard, Jessica; Bonis-Profumo, Gianna; Burkhart, Sarah; Delisle, Aurélie; Diffey, Simon; Eria, Taati; Farmery, Anna; et al. (Food and Agriculture Organization of the United Nations, 2023)
This report is intended for actors, policymakers and funders concerned with improving food and nutrition security with fisheries as an entry point. It is equally valuable for food system, agricultural, health and nutrition actors who are seeking to protect and enhance the benefits that fish and other aquatic foods provide to a diversity of nutrition goals. This report has been developed from an extensive review of published scientific articles and technical reports, as well as interviews and consultations with 17 experts. It also draws upon insights from the Pacific Food System regional dialogues, which were held in the lead-up to the United Nations Food Systems Summit 2021.